Cultural Dynamics in Community Service: Understanding Social Intervention for Better Educational Achievement - Mukhzamilah, Mukhzamilah; Subandiyah, Heny; Nasrullah, Riki; Asteria, Prima Vidya; Shodiq, Syamsul (Proceeding of International Joint Conference on UNESA, 2025)
The community service activities carried out by lecturers of the Indonesian Language and Literature Education Study Program at the International School of Kuala Lumpur, Malaysia, in 2025 serve as a strategic momentum to understand how cultural dynamics influence the success of social interventions. This paper aims to explore in depth the relationship between cultural dynamics and the effectiveness of community service programs within a multicultural education context. This study employs a qualitative approach with a case study method through participatory observation, semi-structured interviews, and document analysis. The findings reveal that cultural dynamics—covering language, social values, communication patterns, and perceptions of educational authority—significantly determine the acceptance, participation, and sustainability of social intervention programs. A cross-cultural understanding–based approach is proven to enhance the effectiveness of community service activities strengthen institutional relationships between universities and international schools, and encourage the internalization of cross-cultural literacy values among students. This article emphasizes that the success of the program in multicultural contexts requires strong intercultural competence, program adaptation to cultural contexts, and inclusive communication strategies. Thus, understanding cultural dynamics is not merely complementary but serves as a fundamental component in designing social interventions to achieve better outcomes.